2020
DOI: 10.1002/cssc.202001362
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Electrocatalytic Water Oxidation by Creating Defects and Lattice‐Oxygen Active Sites on Ni‐Fe Nanosheets

Abstract: Layered nickel-iron oxide/hydroxide nanosheets have proven to be the most efficient catalyst for the water oxidation reaction. Introducing structural defects to the nanosheets is a particularly attractive method for increasing the number of active sites and tailoring the intrinsic electronic properties. Herein, defects were introduced on NiÀ Fe nanosheets through sequentially electrodoping and dedoping the surface of the material with tetramethylammonium ions. The as-prepared defect-rich NiÀ Fe nanosheets show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…[12][13][14][15][16] Among them, surface/ near-surface engineering for modifying the intrinsic properties of the OER electrocatalysts, including the vacancy induction, element doping, sulfidation/phosphatization/nitridation treatment, and plasma activation, etc., are considered to be the most promising and potential approaches. [7,[17][18][19][20][21][22] They can provide a degree of control over the surface/near-surface morphologies, compositions, defect concentrations and even electronic structures of catalyst surfaces at the atomic scale. However, most of them involve rather complex and multiple processing steps in engineering the catalyst surface, such as the specific solvothermal treatment and harsh reaction conditions of elevated pressure and gas environment including some highly aggressive gases (e.g., ammonia, and hydrogen), which would raise the overall cost and hinder the large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Among them, surface/ near-surface engineering for modifying the intrinsic properties of the OER electrocatalysts, including the vacancy induction, element doping, sulfidation/phosphatization/nitridation treatment, and plasma activation, etc., are considered to be the most promising and potential approaches. [7,[17][18][19][20][21][22] They can provide a degree of control over the surface/near-surface morphologies, compositions, defect concentrations and even electronic structures of catalyst surfaces at the atomic scale. However, most of them involve rather complex and multiple processing steps in engineering the catalyst surface, such as the specific solvothermal treatment and harsh reaction conditions of elevated pressure and gas environment including some highly aggressive gases (e.g., ammonia, and hydrogen), which would raise the overall cost and hinder the large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…This defect‐rich structure required an overpotential of 172 mV to obtain the current density of 10 mA cm −2 . [ 113 ] The presence of defects on the electrocatalyst surface suggests the influence of mesoscale diffusion control. In the case of the NiFe LDHs electrocatalyst, which is obtained from NFF through a self‐growth method, it exhibited dynamic changes in surface morphology due to the presence of Ni vacancies.…”
Section: Fabrication Of Self‐supported Fe‐based Oer Electrocatalystsmentioning
confidence: 99%
“…The cooperative interaction between Ni and Fe toward OER catalysis was also realized by doping Fe into Ni(OH) 2 , which offers a more tunable and simpler system compared with NiFe-LDHs. [6][7][8][9] Recently, Kou et al reported that a direct reaction of Fe(NO 3 ) 3 with Ni foam (Ni 0 + NO 3 À + H + ! Ni 2+ + NO 2 À + OH À ) could produce ultrathin Fe-doped Ni(OH) 2 nanosheets that showed further boosted OER activities with a low (0.54 at %) Fe doping.…”
Section: Introductionmentioning
confidence: 99%